Senescence-Associated Secretory Phenotype as a Key Driver of Intestinal Aging: A Narrative Review - Yustina Nuke Ardiyan; Johana Puspasari Dwi Pratiwi (Jurnal Sehat Indonesia (JUSINDO), 2026)
Population aging is accompanied by progressive deterioration of intestinal structure and function, leading to impaired epithelial regeneration, increased intestinal permeability, chronic inflammation, and gut microbiota dysbiosis. Emerging evidence has identified the senescence-associated secretory phenotype (SASP) as a major mediator linking cellular senescence to intestinal aging; however, current evidence remains fragmented. This narrative review aimed to synthesize recent findings regarding the role of SASP in intestinal aging, with particular emphasis on its molecular mechanisms, biological consequences, and potential therapeutic strategies. A literature search was conducted in PubMed using the keywords ("senescence-associated secretory phenotype" OR SASP) AND (gut OR intestin* OR gastrointestin*) AND aging. The initial search identified 113 publications. After title and abstract screening, 60 articles were retained, and the exclusion of review articles and other non-original publications resulted in 28 original studies. Following full-text assessment, 26 articles were included for qualitative synthesis. The available evidence indicates that SASP contributes to intestinal aging by promoting chronic inflammation, impairing intestinal stem cell function, disrupting epithelial barrier integrity, remodeling the extracellular matrix, and altering gut microbiota composition. These interconnected mechanisms create a self-amplifying cycle that accelerates intestinal dysfunction and the loss of tissue homeostasis. Furthermore, emerging senotherapeutic approaches, including senolytics, senomorphics, and microbiota-targeted interventions, show promise in mitigating SASP-mediated intestinal aging. Overall, SASP represents both a key mechanistic driver and a promising therapeutic target for preserving intestinal homeostasis and promoting healthy aging.